معضلة النيوترينو الشمسي و الحل الاهتزازي (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2016)
In this research, we reviewed how to get the relationship of the neutrino oscillation probability in the two flavor approximation, and tested the theoretical model of the oscillation solution. We show that the oscillation probability of neutrino relates with neutrino energy, length of the baseline (the distance between the source and the detector), mixing angle , and square mass difference . This research shows that in order to occur the oscillation of neutrino, it must be at least one of the mass states different of zero. This means that the relationship must be verify. In other words neutrino must have non zero mass. This result holds a huge physical importance. The first regards the Standard Model of elementary particles, which considered neutrino massless. The second regards the OPERA experiment, where neutrino have non zero mass, and cannot spreading fast equal to the speed of light and so this does not agree with the experience of OPERA, which found that the neutrino spreading faster than the speed of light in a vacuum. استعرضنا في هذا البحث كيفية الحصول على علاقة احتمال اهتزاز النيوترينو ثنائي النكهة ، و اختبرنا النموذج النظري للحل الاهتزازي ثنائي النكهة ، تبيّن لنا أن احتمال اهتزاز النيوترينو يتعلق بطاقة النيوترينو، وطول القاعدة (المسافة بين المنبع والكاشف)، و زاوية المزج ، ومربع فرق الكتلة . يوضح هذا البحث أنه من أجل حدوث اهتزاز للنيوترينو ، فإنه يجب أن تكون واحدة على الأقل من حالات الكتلة مختلفة عن الصفر, وهذا يعني أن العلاقة يجب أن تتحقق . بتعبير آخر يجب أن يكون للنيوترينو كتلة غير معدومة ، وهذه النتيجة بحد ذاتها كان لها ارتدادات فيزيائية ضخمة. أولها يخص النموذج المعياري لفيزياء الجسيمات الأولية الذي يعتبر أن النيوترينو بدون كتلة، وثانيها يخص تجربة أوبرا حيث وجود كتلة للنيوترينو تمنعه من الانتشار بسرعة تساوي سرعة الضوء وهذا يناقض ماجاءت به هذه التجربة من أن النيوترينو ينتشر بسرعة أكبر من سرعة الضوء في الخلاء.